(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the stage-by-stage training of cooperative pedagogy in the system of continuous education. At present, humanitarian pedagogy is interpreted as a scientific and theoretical system that considers the student as an active, conscious, equal participant in the educational process and develops him based on his own capabilities.